KONSEP EVALUASI PEMBELAJARAN DALAM PENDIDIKAN ISLAM MENURUT AL-GHAZALI - Arpani Arpani; Dina Hermina; Nuril Huda (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
Evaluation is an important instrument in education especially in learning systems. Evaluation must be carried out effectively so that it can provide real information related to the process and results of learning carried out. al-Ghazali is a figure in the world of Islamic education who certainly has his own views on the concept of evaluation. His views on education have become many references so that a study on the evaluation concept of al-Ghazali's perspective needs to be carried out. This study uses a qualitative approach with the type of library research or library research so that the data used is data derived from the literature relating to the research theme being carried out by the current researcher. The results of this study indicate that the term used by al-Ghazali to represent evaluation is the term al-Hisab/al-Muhasabah which means calculating, assessing, measuring, and correcting. The purpose of learning evaluation in al-Ghazali's view is to obtain information on the results that have been obtained by students, especially on the aspect of child morality so that it can be used as a reference for policy making. The concept of evaluation for Al-Ghazali tends to be more oriented towards how students can solve all the problems of life they find. Armed with the knowledge they have, students are expected to be able to overcome all life problems independently, the teacher's task is to help direct students to the right path, while students are required to be able to overcome them independently. The implication of the results of this research is that educators and students can know properly and correctly about their respective positions, rights and obligations.